(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
In comparison with some European countries such as Germany, Spain, France, and UK, Italy has no end of life legislation even now. From a clinical point of view, there is in western countries today a sound evidence supporting that the best scientific and ethical approach to the end of life issues is based on four fundamental principles: shared decision making process with patient and family; rejection of dying process marked by the suffering anddisproportionate treatments; withholding/withdrawing treatments and palliative sedation as active contributionsto suppress the patient suffering and painat the end of life; clear-cut difference between these clinical and ethical optionsand euthanasia. In this sense, Italian clinicians need a law able to guarantee inend of life setting, the autonomy of doctor-patient-families relationship, respecting the different cultures and religious or nonreligious approachesto life and death,as well as different biographical and biological story of everyone.At the same time, this law should be able also to provide physicians with alegal coverageto make allthe necessary choicesregarding the increasingly complex connection between disease and death and modern clinicalpractice on one hand, and relatedhuman vicissitudes on the other hand.